Coating and method of application thereof

The hot metal thermal insulation coating composition, featuring a combination of hollow glass spheres and an aqueous potassium silicate solution in multiple layers, addresses the limitations of existing coatings by providing enhanced thermal insulation and adhesion to metal surfaces, even at high temperatures.

JP7648189B2Active Publication Date: 2025-03-18FIRST POINT AS
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2022500760
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-07-07
Filing Date
2020-06-09
Publication Date
2025-03-18
Estimated Expiration
2040-06-09

AI Technical Summary

Technical Problem

Existing thermal insulation coatings for metals have limitations such as low resistance to high temperatures, poor adhesion to metal surfaces, and inadequate insulation properties.

Method used

A hot metal thermal insulation coating composition comprising a first layer with hollow glass spheres and an aqueous potassium silicate solution, and a second layer with additional hollow glass spheres, styrene-acrylate dispersion, and carbon black, which provides enhanced thermal insulation, adhesion, and resistance to high temperatures.

Benefits of technology

The coating composition achieves superior thermal insulation, excellent adhesion to metal surfaces even at high temperatures, and improved durability, making it suitable for protecting metal surfaces from extreme heat.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to a coating composition, particularly a coating composition intended for insulating hot metals, which comprises a first layer containing an aqueous solution of silicate and comprising 35-71% by volume of hollow glass spheres, 26-62% by volume of an aqueous potassium silicate solution, 1-3% by volume of an adhesion additive, and 0.1% by volume of a water glass stabilizer, and at least one second layer containing 71-84.6% by volume of hollow glass spheres, 9-22.6% by volume of an aqueous potassium silicate solution, 0.2-0.3% by volume of an adhesion additive, 0.1% by volume of a water glass stabilizer, 2-3% by volume of cut glass fibers, and 1.7-3% by volume of a styrene-acrylate dispersion. A method for applying a coating composition, particularly a coating composition comprising at least one layer containing an aqueous silicate solution, in which a first layer containing 35 to 71% by volume of hollow glass spheres, 26 to 62% by volume of aqueous potassium silicate solution, 1 to 3% by volume of an adhesion additive, and 0.1% by volume of a water glass stabilizer is applied in a first step, and then a second layer containing 71 to 84.6% by volume of hollow glass spheres, 9 to 22.6% by volume of aqueous potassium silicate solution, 0.2 to 0.3% by volume of an adhesion additive, 0.1% by volume of a water glass stabilizer, 2 to 3% by volume of cut glass fibers, and 1.7 to 3% by volume of a styrene-acrylate dispersion is applied on the first layer.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention is Guo and a method for applying the same. [Background technology]

[0002] There are several methods known from the state of the art on how to use paints to enhance the thermal durability of metals.

[0003] One of the known solutions is the use of intumescent paints, the principle of which is based on their volume increase due to the action of heat during combustion at temperatures above 150 ° C, when the paint is used to create a non-combustible insulating layer several centimeters thick that protects the surface of, for example, metal load-bearing structures. Their disadvantages are the high cost, insufficient service life and complex renewability of the paint, since the existing old paint must be removed by abrasive means. The biggest disadvantage, however, is the fact that intumescent paints cannot be covered with other structures, such as linings, bulkheads or ceilings.

[0004] There are also coating compositions based on water glass, for example fire-resistant coating compositions based on water glass. This compound, known from the patent document Czechoslovak Patent Application Publication CS 175548, contains 75-98% by weight of soda water glass or potash water glass with a SiO2 to Na2O molar ratio of 1.8-3.5 or a SiO2 to K2O molar ratio of 2.1-2.3, with a density of 1.3-1.7 at 15 ° C (with soda water glass) and a density of 1.3-1.4 at 15 ° C (with potash water glass), and 2-25% by weight of an aqueous dispersion of acrylic or methacrylic polymethyl esters or polybutyl esters with an average degree of polymerization of 2200-4000 and a polymer-to-water ratio equal to 1:1-1:2. The disadvantage of this coating composition is its lower heat insulating effect and low thermal stability.

[0005] The same drawbacks can be found in the compound forming a protective layer known from the patent document Czechoslovak Patent Publication CS PV 1989-1840. This compound consists of 25-75% by weight of acidic magnesium metasilicate and 25-75% by weight of water glass. It is suitable for protecting metal materials, but also wood and cardboard. This mixture cannot protect the underlying material from extensive heat.

[0006] Another patent document, Czech Patent Application Publication CZ PV2002-2407, describes a silicate coating composition containing water glass or a mixture of water glass and a silicon dioxide salt in a SiOa to alkali metal oxide molar ratio of 5 to 30 moles of SiO2 per mole of alkali metal oxide in addition to one or more organic ammonia compounds and one or more fillers.

[0007] Czech utility model CZ 31096 U describes a mixture for glass-based permeable fire-retardant intumescent insulation materials, which contains 35% by weight of 1-4 mm porous glass spheres, 63% by weight of soda water glass, 1% by weight of carbon black and 1% by weight of hydrophilic alkoxyl alkyl ammonium salt as water glass stabilizer. The disadvantage of this mixture lies in the fact that it cannot be applied directly onto metal, since it will fall off when the temperature exceeds 100 ° C.

[0008] Czech utility model CZ 30925 U presents a mixture for thin-layer insulating and heat-reflecting finishing of hot surfaces. The mixture contains 10-13% by weight of hollow glass spheres with an average size of 0.089 mm, 66-68% by weight of potassium water glass, 2-3% by weight of lithium water glass, 7-12% by weight of water, 1% by weight of hydrophilic alkoxyl alkyl ammonium salt as binder stabilizer, 3-5% by weight of triethanolamine as adhesion additive, 1% by weight of zirconium oxide as thermally expandable filler, 1% by weight of carbon black as thermally expandable filler, 1% by weight of cut glass fibers with a length of 6 mm, 1% by weight of silicon dioxide nanofibers and 1% by weight of silicone defoamer. The viscosity of this mixture resembles a very thick foam suspension and its adhesion to metal surfaces is not very good. This type of mixture has poor adhesion to metal heated above 100 ° C. Generally, this material loses adhesion, elasticity, and thermal expansion at very high temperatures. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] Czechoslovak Patent Publication No. CS175548 [Patent Document 2] Czechoslovak Patent Publication No. CS PV1989-1840 [Patent Document 3] Czech Republic Patent Application No. CZ PV2002-2407 [Patent Document 4] Czech Republic Utility Model No. CZ 31096 U [Patent Document 5] Czech Republic Utility Model No. CZ 30925 U Summary of the Invention [Problem to be solved by the invention]

[0010] From the above existing state of the art (background of the invention) it is evident that the main disadvantages of the hitherto known mixtures are their lower resistance to high temperatures and heat, as well as their lower adhesion to metal surfaces.

[0011] The object of the present invention is to formulate a material for protecting metal components of various structures from high temperatures, which is resistant to high heat for long periods of time, has excellent thermal expansion and adhesion to underlying materials even at high temperatures, and has excellent thermal insulation properties. [Means for solving the problem]

[0012] The above mentioned disadvantages are largely obviated and the object of the present invention is achieved by a coating composition for the thermal insulation of hot metals, containing an aqueous silicate solution according to the present invention, the nature of which consists in the fact that it comprises a first layer comprising 35-71% by volume of hollow glass spheres, 26-62% by volume of an aqueous potassium silicate solution, 1-3% by volume of an adhesion additive and 0.1% by volume of a water glass stabilizer, and at least one second layer comprising 71-84.6% by volume of hollow glass spheres, 9-22.6% by volume of an aqueous potassium silicate solution, 0.2-0.3% by volume of an adhesion additive, 0.1% by volume of a water glass stabilizer, 2-3% by volume of cut glass fibres and 1.7-3% by volume of a styrene-acrylate dispersion. The advantage is that this coating composition has low thermal conductivity and thermal permeability, in addition to which heat dissipation from the hot surface is minimal. The first layer, when applied, has just such a viscosity that it connects itself well to the metal surface and maintains its adhesion and thermal expansion even after being heated to high temperatures. The advantage of the coating composition is the fact that the filler used in the composition is formed from an aqueous solution of potassium silicate (of pure inorganic origin), has excellent thermal insulation capabilities, is antifungal, is highly fire- and heat-resistant, has excellent adhesion to all kinds of surfaces, is easily applied to the surface of the underlying layer, and ensures sufficient hardness and abrasion resistance as well as vapor permeability. After hardening, the material becomes practically a potash water glass, which is resistant to both seawater and freshwater, resistant to acidic and basic solutions and protects the metal surface from corrosion. To increase the elasticity, adhesion and thermal expansion of components with a higher content of glass spheres, a styrene-acrylate dispersion is advantageously used. This dispersion also prevents the silicate filler from being diluted by water, but maintains the excellent adhesion of the composition and improves its quality by creating weak interactions with the polymer chains of the silicate, thereby facilitating the crosslinking process.

[0013] It is advantageous if both layers further contain 1.8-7.5% by volume of water. The advantage of the water present in the layers lies in the fact that it facilitates the application of the composition and increases its thermal insulation capacity.

[0014] It is also very advantageous if both layers additionally contain 0.1-0.4% by volume of carbon black. Carbon black acts as a thermally expandable filler and at the same time blocks the UV, IR and visible light emitted by the hot metal surface, thereby preventing the metal from causing energy losses. Carbon black is added to the mixture in the form of an aqueous solution whose concentration is 25% by weight.

[0015] It is also advantageous that the size of the hollow spheres is in the range of 0.05-0.08 mm. The advantage is that it is possible to create a layer with optimal thermal insulation capacity.

[0016] When triethanolamine is used as an adhesion additive, it is further advantageous since this additive increases the thermal expansion and elasticity of the mixture depending on the thermal expansion of the metal surface.

[0017] It is also advantageous to use a hydrophilic alkoxyalkyl ammonium salt as a water glass stabilizer.

[0018] The density of potassium silicate solution is 1230-1250kg / m 3 and it is even more advantageous if the molar weight ratio of silicon dioxide to potassium oxide in the aqueous potassium silicate solution is in the range of 3.8 to 4.1. The molar weight ratio of silicon dioxide to potassium oxide, and the associated density and concentration of the solution, have a considerable effect on the rheological properties, electrical properties, compressibility and adhesion (similar to electrolytes), as well as hardness and strength of the water glass as a polymer mixture.

[0019] The hollow glass sphere is made of a material containing 70-80% by weight of silicon dioxide, 3-8% by weight of sodium oxide, 8-16% by weight of calcium oxide, and 2-6% by weight of boron oxide, and the specific gravity of the hollow glass sphere is 0.18-0.22 g / cm 3It is also advantageous if the spheres are in the range of 0.1 to 0.5 mm. These spheres have very thin walls. They contact each other at individual points and a large number of sharp material interfaces (boundaries) represent resistance to the passage of heat. Such porous systems distinguish themselves by low thermal conductivity and act as excellent thermal insulating materials.

[0020] It is also advantageous if the cut fibers are made of alkaline zirconium silicate and have a length in the range of 4-10 mm and a diameter in the range of 0.01-0.02 mm. These fibers provide sufficient thermal expansion of the coating composition, as well as its elasticity and adaptability to the underlying metal surface even at very high temperatures.

[0021] The above-mentioned disadvantages are largely eliminated and the object of the present invention is achieved by a method for applying a coating composition, in particular a coating composition consisting of at least one layer containing an aqueous silicate solution according to the present invention, whose nature consists in the fact that, as a first step, a layer (first layer) containing 35-71% by volume of hollow glass spheres, 26-62% by volume of an aqueous potassium silicate solution, 1-3% by volume of an adhesion additive and 0.1% by volume of a water glass stabilizer is applied onto a clean surface, and then a second layer containing 71-84.6% by volume of hollow glass spheres, 9-22.6% by volume of an aqueous potassium silicate solution, 0.2-0.3% by volume of an adhesion additive, 0.1% by volume of a water glass stabilizer, 2-3% by volume of cut glass fibers and 1.7-3% by volume of a styrene-acrylate dispersion is applied onto the first layer.

[0022] The first layer itself can act as an independent insulating layer, but is essentially a layer that can be (advantageously) covered by another layer. The advantage is the fact that the second layer (which is primarily an insulating layer) has optimum conditions with regard to its adhesion and resistance to thermal degradation due to the first layer.

[0023] It is also very advantageous if the second layer is applied onto the first layer after 24 hours or later.

[0024] It is more advantageous if both layers are then heated to a temperature of from 100° C. to 200° C., most advantageously after 24 hours after coating.

[0025] Nevertheless, the most advantageous application method is as follows: apply a first layer and heat it after 24 hours to a temperature of 100°C-200°C for 5 minutes. After the first layer has cooled, apply a second layer and again after 24 hours heat everything to the same temperature for 5 minutes. The most advantageous temperature rise in both cases is 100°C / 10 minutes.

[0026] The main advantage of this coating composition and its application method is the fact that it has a significantly better thermal insulation capacity than the coating compositions known from the state of the art and at the same time has better adhesion, elasticity, thermal expansion and compressibility, even after heating. Another advantage is the fact that the coating composition according to the invention can be easily applied not only to metals, but also to a wide range of materials, for example wall materials. This coating composition has excellent thermal insulation capacity due to the precise distribution curve of the glass microspheres, eliminating the passage of heat and mechanically protecting its surface from external influences and corrosion. The coating composition is non-flammable, vapor-permeable, moisture-resistant, sufficiently hard and wear-resistant. Moreover, it is environmentally friendly and does not harm health. The surface of the coating composition is easily polished and also easily covered with plaster or paint or can easily be provided with any kind of lining, since the volume hardly changes. The durability of the coating composition is good. The coating composition was tested and applied on a surface at 600 ° C, but its temperature was only 50 ° C when touched. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0027] Example 1

[0028] The coating composition for the thermal insulation of hot metals consists of a first layer applied to a thickness of 2 millimeters containing 48% by volume hollow glass spheres, 46.3% by volume potassium silicate aqueous solution, 1.6% by volume adhesion additive (triethanolamine), 0.1% by volume water glass stabilizer (hydrophilic aicoxyl alkyl ammonia salt), 3.8% by volume water, 0.2% by volume carbon black, and a second layer of 10 millimeters thick disposed (applied) on top of the first layer. The second layer contains 74% by volume hollow glass spheres, 15% by volume potassium silicate aqueous solution, 0.2% by volume adhesion additive (triethanolamine), 0.1% by volume water glass stabilizer (hydrophilic aicoxyl alkyl ammonia salt), 2% by volume cut glass fibers, 2% by volume styrene-acrylate dispersion, 6.5% by volume water, and 0.2% by volume carbon black.

[0029] A hydrophilic alkoxyalkyl ammonium salt in the form of a 98% aqueous solution of N,N,N',N'-tetrakis(2-hydroxypropyl)ethylenediamine is used as the water glass stabilizer.

[0030] The size of the hollow glass sphere is 0.065 mm.

[0031] The density of potassium silicate solution is 1240kg / m 3 and the molar weight ratio of silicon dioxide to potassium oxide is 3.9.

[0032] The specific gravity of a hollow glass sphere is 0.2 g / cm 3 and the spheres are made of a material containing, by weight, 75% silicon dioxide, 6% sodium oxide, 15% calcium oxide, and 4% boron oxide.

[0033] The cut glass fiber is 6 mm long, has a diameter of 0.015 mm, and is made of alkaline zirconium silicate.

[0034] The above coating composition is applied as follows: In the first step, a first layer is applied on a clean surface. The first layer contains 48% by volume of hollow glass spheres, 46.3% by volume of potassium silicate aqueous solution, 1.6% by volume of adhesion additive (triethanolamine), 0.1% by volume of water glass stabilizer (hydrophilic alkoxyl alkyl ammonium salt), 3.8% by volume of water, and 0.2% by volume of carbon black. The first layer is then heated to a temperature of 100°C to 200°C for 5 minutes, and after 24 hours of cooling, a second layer is applied on the first layer. The second layer contains 74% by volume hollow glass spheres, 15% by volume aqueous potassium silicate solution, 0.2% by volume adhesion additive (triethanolamine), 0.1% by volume water glass stabilizer (hydrophilic alkoxyl alkyl ammonium salt), 2% by volume cut glass fibers, 2% by volume styrene-acrylate dispersion, 6.5% by volume water, and 0.2% by volume carbon black.

[0035] Then, after 24 hours, both layers are heated to a temperature of 100°C to 200°C for 5 minutes.

[0036] After both layers have cooled, the surface is ground and covered with a coating of paint.

[0037] Example 2

[0038] The coating composition for the thermal insulation of hot metals consists of a first layer applied to a thickness of 1 millimeter containing 65% by volume hollow glass spheres, 26.5% by volume potassium silicate aqueous solution, 2.2% by volume adhesion additive (triethanolamine), 0.1% by volume water glass stabilizer (hydrophilic alkoxyl alkyl ammonia salt), 5.8% by volume water, 0.4% by volume carbon black, and a second layer of 5 millimeters thick disposed (applied) on top of the first layer. The second layer contains 78% by volume hollow glass spheres, 9% by volume potassium silicate aqueous solution, 0.2% by volume adhesion additive (triethanolamine), 0.1% by volume water glass stabilizer (hydrophilic alkoxyl alkyl ammonia salt), 2% by volume cut glass fiber, 3% by volume styrene-acrylate dispersion, 7.5% by volume water, and 0.2% by volume carbon black.

[0039] A hydrophilic alkoxyalkyl ammonium salt in the form of a 98% aqueous solution of N,N,N',N'-tetrakis(2-hydroxypropyl)ethylenediamine is used as the water glass stabilizer.

[0040] The size of the hollow glass sphere is 0.065 mm.

[0041] The density of potassium silicate solution is 1230kg / m 3 and the molar weight ratio of silicon dioxide to potassium oxide is 3.8.

[0042] The specific gravity of a hollow glass sphere is 0.18 g / cm 3 and the spheres are made of a material containing, by weight, 75% silicon dioxide, 6% sodium oxide, 15% calcium oxide, and 4% boron oxide.

[0043] The cut glass fiber is 4 mm long and has a diameter of 0.01 mm, and is made of alkaline zirconium silicate.

[0044] The above coating composition is applied as follows: in the first step, a first layer is applied on a clean surface. The first layer contains 65% by volume of hollow glass spheres, 26.5% by volume of potassium silicate aqueous solution, 2.2% by volume of adhesion additive (triethanolamine), 0.1% by volume of water glass stabilizer (hydrophilic alkoxyl alkyl ammonium salt), 5.8% by volume of water, and 0.4% by volume of carbon black. The first layer is then heated to a temperature of 100°C to 200°C for 5 minutes, and after 24 hours of cooling, a second layer is applied on the first layer. The second layer contains 78% by volume hollow glass spheres, 9% by volume aqueous potassium silicate solution, 0.2% by volume adhesion additive (triethanolamine), 0.1% by volume water glass stabilizer (hydrophilic alkoxyl alkyl ammonium salt), 2% by volume cut glass fibers, 3% by volume styrene-acrylate dispersion, 7.5% by volume water, and 0.2% by volume carbon black.

[0045] Then, after 24 hours, both layers are heated to a temperature of 100°C to 200°C for 5 minutes.

[0046] After both layers have cooled, the surface is ground and covered with a coating of paint.

[0047] Example 3

[0048] The coating composition for the thermal insulation of hot metals consists of a first layer applied to a thickness of 3 millimeters containing 35% by volume hollow glass spheres, 62% by volume potassium silicate aqueous solution, 1% by volume adhesion additive (triethanolamine), 0.1% by volume water glass stabilizer (hydrophilic alkoxyl alkyl ammonia salt), 1.8% by volume water, 0.1% by volume carbon black, and a second layer of 10 millimeters placed (applied) on top of the first layer. The second layer contains 71% by volume hollow glass spheres, 18% by volume potassium silicate aqueous solution, 0.3% by volume adhesion additive (triethanolamine), 0.1% by volume water glass stabilizer (hydrophilic alkoxyl alkyl ammonia salt), 3% by volume cut glass fibers, 1.7% by volume styrene-acrylate dispersion, 5.5% by volume water, and 0.4% by volume carbon black.

[0049] A hydrophilic alkoxyalkyl ammonium salt in the form of a 98% aqueous solution of N,N,N',N'-tetrakis(2-hydroxypropyl)ethylenediamine is used as the water glass stabilizer.

[0050] The size of the hollow glass sphere is 0.065 mm.

[0051] The density of potassium silicate solution is 1250kg / m 3 and the molar weight ratio of silicon dioxide to potassium oxide is 4.1.

[0052] The specific gravity of a hollow glass sphere is 0.18 g / cm 3 and the spheres are made of a material containing, by weight, 75% silicon dioxide, 6% sodium oxide, 15% calcium oxide, and 4% boron oxide.

[0053] The cut glass fiber is 10 mm long, has a diameter of 0.02 mm, and is made of alkaline zirconium silicate.

[0054] The above coating composition is applied as follows: in the first step, a first layer is applied on a clean surface. The first layer contains 35% by volume of hollow glass spheres, 62% by volume of potassium silicate aqueous solution, 1% by volume of adhesion additive (triethanolamine), 0.1% by volume of water glass stabilizer (hydrophilic alkoxyl alkyl ammonium salt), 1.8% by volume of water, and 0.1% by volume of carbon black. The first layer is then heated to a temperature of 100°C to 200°C for 5 minutes, and after 24 hours of cooling, a second layer is applied on the first layer. The second layer contains 71% by volume hollow glass spheres, 18% by volume aqueous potassium silicate solution, 0.3% by volume adhesion additive (triethanolamine), 0.1% by volume water glass stabilizer (hydrophilic alkoxyl alkyl ammonium salt), 3% by volume cut glass fibers, 1.7% by volume styrene-acrylate dispersion, 5.5% by volume water, and 0.4% by volume carbon black.

[0055] Then, after 24 hours, both layers are heated to a temperature of 100°C to 200°C for 5 minutes.

[0056] After both layers have cooled, the surface is ground and covered with a coating of paint. [Industrial Applicability]

[0057] The coating compositions according to the invention can be used in particular for the thermal protection of hot metal surfaces, for example for the thermal protection of the surfaces of steam pipelines, flue pipes, furnaces, refrigeration plants and heating, ventilation and air conditioning equipment.

Claims

1. A first layer containing 35-71% by volume of hollow glass spheres, 26-62% by volume of an aqueous potassium silicate solution, 1-3% by volume of an adhesion additive, and 0.1% by volume of a water glass stabilizer; at least one second layer containing 71-84.6% by volume of hollow glass spheres, 9-22.6% by volume of an aqueous potassium silicate solution, 0.2-0.3% by volume of an adhesion additive, 0.1% by volume of a water glass stabilizer, 2-3% by volume of cut glass fibers, and 1.7-3% by volume of a styrene-acrylate dispersion; The density of the aqueous solution of potassium silicate is in the range of 1230 to 1250 kg / m 3 ; the adhesion additive is triethanolamine; A coating characterized in that said water glass stabilizer is a hydrophilic alkoxylalkyl ammonium salt.

2. 10. The coating of claim 1, wherein the individual layers further comprise 1.8 to 7.5 volume percent water.

3. The coating of claim 1 or 2, wherein the layers further comprise 0.1 to 0.4 volume percent carbon black.

4. 4. The coating according to claim 1, wherein the size of the hollow glass spheres is in the range of 0.05 to 0.08 mm.

5. 5. Coating according to any one of claims 1 to 4, characterized in that the molar ratio of silicon dioxide to potassium oxide in the aqueous solution of potassium silicate is in the range of 3.8 to 4.

1.

6. 6. The coating according to claim 1, wherein the hollow glass spheres contain 70-80% by weight of silicon dioxide, 3-8% by weight of sodium oxide, 8-16% by weight of calcium oxide, and 2-6% by weight of boron oxide.

7. The specific gravity of the hollow glass sphere is 0.18 to 0.22 g / cm 3 7. The coating of claim 1, wherein the coating has a viscosity of 100:1 or more.

8. 8. The coating of claim 1, wherein the cut glass fibers are made of alkaline zirconium silicate.

9. The coating according to any one of claims 1 to 8, characterized in that the cut glass fibres have a length in the range of 4 to 10 mm and a diameter in the range of 0.01 to 0.02 mm.

10. A method for applying the coating according to any one of claims 1 to 9, comprising the steps of: applying, as a first step, the first layer, which contains 35 to 71 vol. % of the hollow glass spheres, 26 to 62 vol. % of the potassium silicate aqueous solution, 1 to 3 vol. % of the adhesion additive, and 0.1 vol. % of a water glass stabilizer, onto a surface of the lower layer; and then applying a second layer onto the first layer, the second layer containing 71-84.6% by volume of the hollow glass spheres, 9-22.6% by volume of the aqueous potassium silicate solution, 0.2-0.3% by volume of the adhesion additive, 0.1% by volume of the water glass stabilizer, 2-3% by volume of the cut glass fibers, and 1.7-3% by volume of the styrene-acrylate dispersion.

11. 11. The method of claim 10, wherein the second layer is applied over the first layer after 24 hours or more.

12. A method for applying a coating according to claims 10 or 11, characterized in that both said layers are then heated to a temperature of between 100°C and 200°C.

13. A method for applying a coating according to claim 11 or 12, characterized in that both said layers are subsequently heated to a temperature of between 100° C. and 200° C. after 24 hours or more.

Citation Information

Patent Citations

  • fire protective coating based on water glass

    CS175548B1

  • CSPV1989

  • A mixture for thin-layer heat-insulating thermoreflection treatment of hot surfaces with fibres

    CZ30925U1

  • A mixture for a breathable, fire retardant, lightweight thermal insulation system based on glass

    CZ31096U1

  • CZPV2002-2407